Exploring How Digital Financial Literacy Affects Fintech Credit Behavior through Psychological and Digital Financial Access - Ni Iffah Kesuma; Sumiati; Nur Khusniyah Indrawati (Jurnal Dinamika Manajemen, 2025)
This study investigates the influence of digital financial literacy on the credit behavior of Generation Z as fintech users, with digital financial inclusion and internal locus of control as mediating variables. Using a quantitative approach with 150 respondents in Malang, data were collected through an online questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings demonstrate that digital financial literacy significantly affects credit behavior both directly and indirectly, with mediation confirming the crucial role of financial inclusion and psychological control. This research provides novelty by integrating digital financial literacy, financial ecosystem access, and psychological factors into a single framework for understanding Gen Z’s credit behavior. Theo retically, it enriches behavioral finance literature, while practically, it emphasizes the need for policymakers and fintech institutions to design targeted programs that strengthen financial decision-making among younger generations.